SISTEM INFORMASI KEUANGAN BERBASIS WEB DI KANTOR NOTARIS DAN PPAT SULISTIYANI,S.H.,M.Kn - Anita Nur Setiyani; Ahmad Ashifuddin Aqham; Munifah; Edy Siswanto (LPPM Politeknik Pratama Kendal, 2025)
An The development of information significantly impacts the legal field, particularly in the administration and financial management of the Notary and PPAT Office of Sulistiyani, S.H., M.Kn. The conventional methods used often lead to errors and reporting delays. This research aims to develop a computer-based financial information system using the Research and Development (R&D) method. The system is designed to improve efficiency, accuracy, and data security. The results show that the developed system successfully minimizes recording errors and accelerates the financial reporting process. In conclusion, the implementation of this computer-based information system is effective and efficient in supporting the notary office's financial management.